Cultural values and prosocial behavior among Saudi undergraduates: the mediating role of empathy - Abdullah, Alsalman Arwa; Hamsan, Hanina Halimatusaadiah; Ma'rof, Aini Azeqa (Advanced Scientific Research, 2020)
Cultural values and empathy are considered as crucial factors that influence prosocial behavior. However, this issue has not been extensively investigated within a Saudi sample. Students at three universities in Riyadh Region of Saudi Arabia (N=394) participated in the prosocial behavior survey, whereby the prosocial behavior scale (PBC), twenty item values inventory (TwIVI), Toronto Empathy Questionnaire (TEQ) were used. Using pearson correlation, and mediation analysis (process by hayes), the relationship between cultural values and empathy was investigated, and the results showed that cultural values have relationships with empathy. It also found that undergraduates with high scores in empathy were also found to score more highly on prosocial behavior. Additionally, cultural values were found to be associated with prosocial behavior. Furthermore, the results revealed that the correlation between benevolence and prosocial behavior is mediated by empathy.